2023
DOI: 10.1111/pbi.14201
|View full text |Cite
|
Sign up to set email alerts
|

The elicitor VP2 from Verticillium dahliae triggers defence response in cotton

Ping Qiu,
Baoxin Zheng,
Hang Yuan
et al.

Abstract: SummaryVerticillium dahliae is a widespread and destructive soilborne vascular pathogenic fungus that causes serious diseases in dicot plants. Here, comparative transcriptome analysis showed that the number of genes upregulated in defoliating pathotype V991 was significantly higher than in the non‐defoliating pathotype 1cd3‐2 during the early response of cotton. Combined with analysis of the secretome during the V991–cotton interaction, an elicitor VP2 was identified, which was highly upregulated at the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
0
0
Order By: Relevance
“…Only 3.6% (fifty) of the unique DEGs from the time series were found to be in common between MCU-5 and Siokra 1-4, highlighting the different transcriptional responses of these two cultivars. Previous transcriptome and cytological investigations comparing resistant and susceptible cotton varieties to VW have been performed [59][60][61][62][63][64][65] and found that resistant lines often contain more terpenoids and phenolics than susceptible varieties that are detected earlier in roots of the resistant as compared to the susceptible line. Guo et al [66] found that the expression of an ethylene response-related factor (GbERF1) improved VW resistance in cotton via activation of lignin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3.6% (fifty) of the unique DEGs from the time series were found to be in common between MCU-5 and Siokra 1-4, highlighting the different transcriptional responses of these two cultivars. Previous transcriptome and cytological investigations comparing resistant and susceptible cotton varieties to VW have been performed [59][60][61][62][63][64][65] and found that resistant lines often contain more terpenoids and phenolics than susceptible varieties that are detected earlier in roots of the resistant as compared to the susceptible line. Guo et al [66] found that the expression of an ethylene response-related factor (GbERF1) improved VW resistance in cotton via activation of lignin synthesis.…”
Section: Discussionmentioning
confidence: 99%